2004
DOI: 10.1063/1.1782275
|View full text |Cite
|
Sign up to set email alerts
|

Absorbing film assisted laser induced forward transfer of fungi (Trichoderma conidia)

Abstract: We present an investigation on absorbing film assisted laser induced forward transfer (AFA-LIFT) of fungus (Trichoderma) conidia. A KrF excimer laser beam [λ=248nm,FWHM=30ns (FWHM, full width at half maximum)] was directed through a quartz plate and focused onto its silver coated surface where conidia of the Trichoderma strain were uniformly spread. The laser fluence was varied in the range of 0–2600mJ∕cm2 and each laser pulse transferred a pixel of target material. The average irradiated area was 8×10−2mm2. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(68 citation statements)
references
References 25 publications
(14 reference statements)
1
67
0
Order By: Relevance
“…10 Moreover, LIFT can be used for printing different complex materials, such as inorganic inks or pastes, 11 organic polymers, 12 and even biological solutions. 8,[13][14][15] The feasibility of the technique for depositing these materials has been proved through the fabrication of diverse functional devices such as microbatteries, 11 solar cells, 16 organic light-emitting diodes, 17 or biosensors. 18,19 Such interesting features prompted several studies on the transfer process which takes place during the LIFT of liquids.…”
Section: Introductionmentioning
confidence: 99%
“…10 Moreover, LIFT can be used for printing different complex materials, such as inorganic inks or pastes, 11 organic polymers, 12 and even biological solutions. 8,[13][14][15] The feasibility of the technique for depositing these materials has been proved through the fabrication of diverse functional devices such as microbatteries, 11 solar cells, 16 organic light-emitting diodes, 17 or biosensors. 18,19 Such interesting features prompted several studies on the transfer process which takes place during the LIFT of liquids.…”
Section: Introductionmentioning
confidence: 99%
“…2 In recent years, significant study has been directed towards extending the range of materials that can be deposited using LIFT; metals, 3 oxides, 2 superconductors, 4 DNA, 5 proteins, 6 fungal spores, 7 polycrystalline Si, 8 and various important electronic and sensing materials 9 have all been transferred. In contrast, efforts to reduce the minimum achievable deposition dimensions have received comparatively little attention.…”
mentioning
confidence: 99%
“…Then, the transferred materials can be more efficiently thrust to the receiver. Several materials such as Ti [35], polymer [37], and Ag [38] have been used as the thrust material in various LIFT experiments previously. Besides, according to our previous work [34], we have found that Ge 2 Sb 2 Te 5 can be laser ablated and subsequently transferred with relatively lower fs-laser fluence.…”
Section: Introductionmentioning
confidence: 99%